2018
DOI: 10.4274/mjima.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Colistin Heteroresistance and Some Factors Affecting Heteroresistance in Carbapenem-Resistant A. baumannii Strains

Abstract: Introduction: Colistin can be used in patients infected with carbapenem-resistant Acinetobacter baumannii complex (CR-ABC), but recently resistance to colistin and heteroresistance have been reported. In this study we aimed to investigate the colistin heteroresistance rates and the effects of colistin and its combinations on colistin heteroresistance/resistance development in CR-ABC strains in our hospital. Materials and Methods: Heteroresistance analysis was performed on CR-ABC isolates and standard ABC strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
17
1
1
Order By: Relevance
“…It is known that in low concentrations colistin is not effective, that is because in 2012, optimal dosage regimens for colistin were updated and increased up to three times [1]. Heteroresistance to colistin among MDR acinetobacter strains was known for more than a decade [19,20,21,22]. While lower doses could cause treatment failure and selection of heteroresistant clones, increased dose could become nephrotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that in low concentrations colistin is not effective, that is because in 2012, optimal dosage regimens for colistin were updated and increased up to three times [1]. Heteroresistance to colistin among MDR acinetobacter strains was known for more than a decade [19,20,21,22]. While lower doses could cause treatment failure and selection of heteroresistant clones, increased dose could become nephrotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Combined therapies have synergistic effects and they could be less toxic due to administration of decreased doses of two antimicrobials. The most frequently studied in-vitro combinations were colistin with rifampicin [21,23], colistin with carbapenems [24] and colistin with tigecycline [21,25]. All these three combinations have synergistic activity against heteroresistant A.baumanni isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endolysins have been recognized in the US "National Action Plan for Combating Antibiotic-resistant Bacteria" 24 , which identified the use of "phage-derived lysins to kill specific bacteria while preserving the microbiota" as a key strategy to reduce the development of antimicrobial resistance due to www.nature.com/scientificreports www.nature.com/scientificreports/ the absence of toxicity in human cells 25,26 . Moreover, some endolysins have been found to display activity against sub-populations of microbes 27,28 extracted from biofilm [29][30][31] and to be useful in other innovative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…baumannii 25 clinical isolates (22 STs) from the II Spanish Multicentre Study (GEIH-REIPI Acinetobacter baumannii 2000-2010) (Accession number Genbank PRJNA422585) 27 Pseudomonas aeruginosa 25 clinical isolates (ST274 [n = 15]; ST1089 [n = 3]; ST not known [n = 7])28 Description of the bacterial strains, plasmids and primers used in this study. Abbreviations: ST; multilocus sequence type.…”
mentioning
confidence: 99%
“…Various studies from clinical settings throughout the world have indicated the emergence of colistin-resistant AB as an important healthcare problem [10,14]. Colistin-susceptible AB strains can easily transform into colistin-resistant or heteroresistant clones, or colistin heteroresistant strains can transform into colistin-resistant clones via exposure to colistin [15][16][17][18]. In 2016, the emergence of plasmid-mediated colistin resistance in an E. coli strain by the MCR-1 mechanism was reported from China, which made scientists focus on the urgent need for global action in the fight against pan-drug-resistant Gram-negative bacteria [19].…”
Section: Introductionmentioning
confidence: 99%